Land of cemetery: funereal images in the poetry of Musa Idris Okpanachi - Uchechukwu Peter Umezurike (Tydskrif vir Letterkunde, 2018)
This paper focuses on Musa Idris Okpanachi’s poetry: The Eaters of the Living (2007), From the Margins of Paradise (2012), and Music of the Dead (2016). Nigeria, even after the military had relinquished power over a decade ago, is still faced with the issues that provoked the trope of protest in much of the poetry published between the mid-eighties and late nineties. Okpanachi’s poetry revisits these issues, demonstrating that democracy has been no less horrifying than military despotism. Dark, haunting images of blood, corpses, and cemetery recur in all three collections, depicting the regularity of death in the nation. I argue that Okpanachi employs funereal imagery to comment on the state’s morbid relationship with its citizenry. The Nigerian state is represented as murderous, so death fulfills its political objective. I conclude that although Okpanachi articulates a cynical commentary on postcolonial Nigeria, he marshals his creative energies to illuminate the political moment of his time.